Convenient Synthesis of 2‐Amino‐4H‐chromenes from Photochemically Generated o‐Quinone Methides and Malononitrile. (1st May 2014) - Fujiwara, Makoto; Sakamoto, Masanori; Komeyama, Kimihiro; Yoshida, Hiroto; Takaki, Ken
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>